Pregnane-based steroids are novel positive NMDA receptor modulators that may compensate for the effect of loss-of-function disease-associated GRIN mutations - Kysilov, Bohdan; Hrcka Krausova, Barbora; Vyklicky, Vojtech; Smejkalova, Tereza; Korinek, Miloslav; Horak, Martin; Chodounska, Hana; Kudova, Eva; Cerny, Jiri; Vyklicky, Ladislav (British journal of pharmacology, 2022)
BACKGROUND AND PURPOSE: N-methyl-D-aspartate receptors (NMDARs) play a critical role in synaptic plasticity, and mutations in human genes encoding NMDAR subunits have been described in individuals with various neuropsychiatric disorders. Compounds with a positive allosteric effect are thought to compensate for reduced receptor function. EXPERIMENTAL APPROACH: We have used whole-cell patch-clamp electrophysiology on recombinant rat NMDARs and human variants found in individuals with neuropsychiatric disorders, in combination with in silico modelling, to explore the site of action of novel epipregnanolone-based NMDAR modulators. KEY RESULTS: Analysis of the action of 4-(20-oxo-5β-pregnan-3β-yl) butanoic acid (EPA-But) at the NMDAR indicates that the effect of this steroid with a "bent" structure is different from that of cholesterol and oxysterols and shares a disuse-dependent mechanism of NMDAR potentiation with the "planar" steroid 20-oxo-pregn-5-en-3β-yl sulfate (PE-S). The potentiating effects of EPA-But and PE-S are additive. Alanine scan mutagenesis identified residues that reduce the potentiating effect of EPA-But. No correlation was found between the effects of EPA-But and PE-S at mutated receptors that were less sensitive to either steroid. The relative degree of potentiation induced by the two steroids also differed in human NMDARs carrying rare variants of hGluN1 or hGluN2B subunits found in individuals with neuropsychiatric disorders, including intellectual disability, epilepsy, developmental delay, and autism spectrum disorder. CONCLUSION AND IMPLICATIONS: Our results show novel sites of action for pregnanolones at the NMDAR and provide an opportunity for the development of new therapeutic neurosteroid-based ligands to treat diseases associated with glutamatergic system hypofunction.
Keywords: NMDA receptor; Steroids; positive allosteric modulator; pregnany; mutace; poruchy autistického spektra; GRIN channelopathy; krysa rodu Rattus; steroids; Animals; Autism Spectrum Disorder; zvířata; Rats; Pregnanes; steroidy; Mutation; transmembrane domain; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu